Communication Research, the Geopolitics of Knowledge and Publishing in High-Impact Journals: The Chronicle of a Commodification Process Foretold - Víctor Manuel Marí Sáez; Clara Martins do Nascimento (tripleC: Communication, Capitalism & Critique)
The reforms in higher education that have been introduced on a global scale in recent years have gone hand in glove with the progressive imposition of scientific journal impact factors, all of which points to the rise of academic capitalism and digital labour in universities that is increasingly subject to the logic of the market. A diachronic analysis of this process allows for talking about, paraphrasing Gabriel García Márquez, the chronicle of a commodification process foretold. More than twenty years ago it was clear what was going to happen, but not how it was going to unfold. Accordingly, this article reconstructs that process, comparing the Spanish case with global trends and highlighting the crucial role that governmental agencies like the National Agency for Quality Assessment and Accreditation and specific evaluation tools like the publication of scientific papers in high-impact journals have played in it. In this analysis, Wallerstein’s core-periphery relations and the concept of commodity fetishism, as addressed by Walter Benjamin, prove to be especially useful. The main research question posed in this article is as follows: What does the process of the commodification of communication research look like in Spain?